Variation in quality of grains used in malting and brewing - Fox, Glen P.; Bettenhausen, Harmonie M. (Frontiers in Plant Science, 2023)
Cereal grains have been domesticated largely from food grains to feed and malting grains. Barley (Hordeum vulgare L. ) remains unparalleled in its success as a primary brewing grain. However, there is renewed interest in “alternative” grains for brewing (and distilling) due to attention being placed on flavor, quality, and health (i.e., gluten issues) aspects that they may offer. This review covers basic and general information on “alternative grains” for malting and brewing, as well as an in-depth look at several major biochemical aspects of these grains including starch, protein, polyphenols, lipids, etc. These traits are described in terms of their effects on processing and flavor, as well as the prospects for improvement through breeding. These aspects have been studied extensively in barley, but little is known about the functional properties in other crops for malting and brewing. In addition, the complex nature of malting and brewing produces a large number of brewing targets but requires extensive processing, laboratory analysis and accompanying sensory analysis. But if a better understanding of the potential of alternative crops that can be used in malting and brewing is needed, then significantly more research is required.